Effect of Lactobacillus casei and Garlic Powder Administration on Broiler Performance, Immune Response and Blood Profile - Istna Mangisah; V D Yunianto; S Sumarsih; S Sugiharto (Indonesian Center for Animal Research and Development (ICARD), 2022)
This study aimed to examine effect of giving a mixture of Lactobacillus casei and garlic powder (LGP) on broiler performance, immune response and blood profile. One hundred and forty-day old broilers with an average body weight of 43.70 ± 0.88 g were placed randomly in 20 experimental units. Completely randomized design was used in this study, with 4 treatments and 5 replications. The treatment was conducted when the chickens were 22-35 days old (finisher phase). The chickens were given a mixture of Lactobacillus casei and garlic powder (LGP) at concentration levels of: 0, 1, 2, and 3%. Parameters measured were blood profile, weight of lymphoid organs (bursa of Fabricius, spleen, and thymus), and carcass production. Data were analyzed for variance and if there was a significant effect, then Duncan’s multiple range test was followed at the 5% level. Results showed that the administration of LGP improved the immune response, carcass weight and final body weight of broiler chickens. The administration of 3% LGP improved immune response and achieved the best broiler performance.